Properties of sputtered full Heusler alloy Cr2MnSb and its application in a magnetic tunnel junction. (20th September 2019) - Gupta, S; Matsukura, F; Ohno, H
Abstract: We deposit 30 nm thick Cr2 MnSb films on a MgO(0 0 1) substrate by magnetron sputtering. X-ray diffraction reveals that the annealing promotes the crystallization of Cr2 MnSb from amorphous at as-deposited state to partially crystallized phase, and that the crystallinity improves by raising the annealing temperature. The crystallized phase exhibits full B 2 and partial L 21 ordering after the annealing above 300 °C. The magnetic and magneto-transport properties reveal that the annealed Cr2 MnSb shows magnetic ordering up to ~350 K with small magnetic moment, 0.3 µ B /formula unit for the sample annealed at 300 °C. We adopt Cr2 MnSb as one of the electrodes in magnetic tunnel junctions (MTJs), and observe the switching of junction resistance, when the magnetization direction is reversed by sweeping an external magnetic field.